Answer:
Add the square of half of the coefficient of [tex]x[/tex] to both sides
[tex]\left(-\dfrac92\right)^2=\dfrac{81}{4}[/tex]
Completing the square:
Rewrite [tex]x^2-9x+2=0[/tex] in the form [tex]y=(x-b)^2 +c[/tex]
Add the square of half of the coefficient of [tex]x[/tex] to both sides:
[tex]\implies x^2-9x+2+\left(-\dfrac92\right)^2=\left(-\dfrac92\right)^2[/tex]
[tex]\implies x^2-9x+2+\dfrac{81}{4}=\dfrac{81}{4}[/tex]
[tex]\implies\left(x-\dfrac92\right)^2 +2=\dfrac{81}{4}[/tex]
[tex]\implies\left(x-\dfrac92\right)^2 +2-\dfrac{81}{4}=0[/tex]
[tex]\implies\left(x-\dfrac92\right)^2 -\dfrac{73}{4}=0[/tex]
[tex]\implies\left(x-\dfrac92\right)^2 -\dfrac{73}{4}=0[/tex]